2015
DOI: 10.1103/physrevc.92.054320
|View full text |Cite
|
Sign up to set email alerts
|

Population ofBe13in a nucleon exchange reaction

Abstract: The neutron-unbound nucleus 13 Be was populated with a nucleon-exchange reaction from a 71 MeV/u secondary 13 B beam. The decay energy spectrum was reconstructed using invariant mass spectroscopy based on 12 Be fragments in coincidence with neutrons. The data could be described with an s-wave resonance at Er = 0.73(9) MeV with a width of Γr = 1.98(34) MeV and a d-wave resonance at Er = 2.56(13) MeV with a width of Γr = 2.29(73) MeV. The observed spectral shape is consistent with previous one-proton removal rea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
(65 reference statements)
1
13
0
Order By: Relevance
“…The relative cross-section for nucleon exchange was an order of magnitude smaller than the 1p knockout, consistent with Ref. [37]. Based on this test case, we estimate that our simulation of single neutron scattering cross-talk is accurate within 33%.…”
Section: Simulationsupporting
confidence: 88%
See 4 more Smart Citations
“…The relative cross-section for nucleon exchange was an order of magnitude smaller than the 1p knockout, consistent with Ref. [37]. Based on this test case, we estimate that our simulation of single neutron scattering cross-talk is accurate within 33%.…”
Section: Simulationsupporting
confidence: 88%
“…Although we expect the majority of the events with two neutron interactions to be caused by a single neutron scattering, there could be a small contribution from a nucleon-exchange reaction that would populate 13 Be and then decay via the emission of two neutrons. Marks, et al found that such a reaction occurred with a cross-section one order of magnitude smaller than one-proton knockout in this region [37]. Assuming that this reaction was also the cause of the small background necessary for fitting the ungated two-body decay energy spectrum, we used the simulation reported in Ref.…”
Section: Simulationmentioning
confidence: 99%
See 3 more Smart Citations